The Confluence of Pornography, Peer Pressure, and Home Environment on Senior Secondary School Students Sexual Behaviour, Counselling Implications - Adeoye, Hammed; Muraina, Kamilu (NIU Journal of Social Sciences, 2019)
This study investigated confluence of pornography, peer pressure and home environment on senior secondary school adolescents' sexual behaviour in Ibadan metropolis, Nigeria. The descriptive research design of ex-post-facto type was adopted for the study. Three hundred (300) participants randomly selected from five (5) Local Government Areas in Ibadan participated in the study. The study considered and answered three research questions. The results showed that senior secondary school adolescents' sexual behaviour is significantly correlated with pornography (r = .756; p<.05); peer pressure (r = .793; p<.05) and home environment (r = .819; p<.05), the independent variables when pulled together have significant effect on sexual behaviour (R (adjusted) =.858 and R2 (adjusted) =.735) with 73.5% of independent variables accounted for adolescents' sexual behaviour. In term of magnitude of contribution home environment made the most significant contribution (Beta= 1.691; t= 15.341; p<0.05) to the prediction of senior secondary school adolescents' sexual behaviour followed by pornography (Beta= 1.525; t= 13.649; p<0.05) and peer pressure (Beta= 1.423; t= 11.007; p<0.05) consecutively. This result has a lot of implications for counselling, It is therefore recommended that the parents/guardians should be trained in the need to monitor the adolescents and also on how to give adequate emotional care. School Counsellors should be made to intensify effort by organising seminars/workshop on the implications of these factors (pornography, peer pressure, and home environment among others) on the adolescents' sexual behaviour in the society. Keywords: Confluence, Pornography, Peer Pressure, Home Environment, Adolescent, Sexual Behaviour.